Simulated Comparison of the Pharmacodynamics of Ciprofloxacin and Levofloxacin Against Pseudomonas aeruginosa Using Pharmacokinetic Data from Healthy Volunteers and 2002 Minimum Inhibitory Concentration Data - Burgess, David S.; Hall, Ronald G. (Clinical therapeutics, 2007)
Background: Until the 2002 approval of levofloxacin 750 mg QD, ciprofloxacin was the fluoroquinolone of choice against Pseudomonas aeruginosa infections. Objective: This study evaluated the AUC:MIC ratios for ciprofloxacin 400 mg BID and TID and levofloxacin 750 mg QD, all administered intravenously, against P aeruginosa using a Monte Carlo simulation. Methods: Pharmacokinetic data for ciprofloxacin and levofloxacin and 2002 MIC distributions against P aeruginosa were obtained from studies in healthy volunteers published in the peer-reviewed literature. Pharmacokinetic studies of each agent were identified by separate MEDLINE searches combining the MeSH heading pharmacokinetics with the generic name of the antimicrobial. Only human studies published in English between 1990 and 2001 were included. Included studies also had to meet 3 minimum criteria: evaluation of clinically relevant dosing regimens, use of rigorous study methods, and provision of mean (SD) values for the pharmacokinetic parameters of interest. When multiple studies met these criteria, a single study was selected for each antimicrobial regimen. Pharmacodynamic analysis was performed using a Monte Carlo simulation of 10,000 patients by integrating the pharmacokinetic parameters, their variability, and 2002 MIC distributions for each antimicrobial regimen. The probability of target attainment was determined for each regimen for an AUC:MIC ratio from 0 to 300. A ≥90% probability of target attainment was considered satisfactory. Results: For ciprofloxacin 400 mg TID and levofloxacin 750 mg QD, the AUC:MIC ratio at the corresponding 2002 Clinical Laboratory Standards Institute break points of 1 and 2 μg/mL were 33 and 34, respectively. The probabilities of target attainment for a free AUC:MIC ratio >90 (equivalent to a total AUC:MIC ratio ≥125) were 47% for ciprofloxacin 400 mg BID, 54% for ciprofloxacin 400 mg TID, and 48% for levofloxacin 750 mg QD. Condusion: When pharmacokinetic data from healthy volunteers and 2002 MIC data were used, none of the simulated fluoroquinolone regimens achieved a high likelihood of target attainment against P aeruginosa.